The Analysis Of Influential Factors Of Halal Supply Chain Management Implementation In Banda Aceh's Hotels - Sentia, Prima Denny; Zuhri, Sarika; Asmadi, Didi; Farhan, Farhan (Univeristas Islam Bandung, 2022)
Aceh is a province in Indonesia that implements Islamic law in its territory and is regulated by Qanun decree. Aceh Qanun No. 8/2016 confirms the determination of the halal product guarantee system. However, the Qanun lacks presenting, regulating, and providing Halal Supply Chain Management (HSCM). The data used in this research was obtained and observed from several Hotels in Banda Aceh that have implemented Halal Certification accreditation. This Research aims to implement multiple linear regression as an approach to review the implementation of HSCM at hotel food service by looking at the interrelationship of the contributing factor in HSCM. There are seven relationships between variables that form hypotheses, namely halal management, quality and hygiene of halal food, halal warehousing, halal transportation, halal raw materials, halal production facilities, and halal suppliers. ANOVA testing (F-test) shows that all factors influence HSCM. However, Partial testing (T-test) shows that the most influential factors on HSCM are given by halal management and halal warehousing.